2015
DOI: 10.1086/682217
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Iron Therapy in Patients with Idiopathic Pulmonary Arterial Hypertension and Iron Deficiency

Abstract: In patients with idiopathic pulmonary arterial hypertension (iPAH), iron deficiency is common and has been associated with reduced exercise capacity and worse survival. Previous studies have shown beneficial effects of intravenous iron administration. In this study, we investigated the use of intravenous iron therapy in iron-deficient iPAH patients in terms of safety and effects on exercise capacity, and we studied whether altered exercise capacity resulted from changes in right ventricular (RV) function and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 32 publications
5
105
0
2
Order By: Relevance
“…It has been suggested that iron deficiency is not just a marker of severity, but independently contributes to poor prognosis and exercise function [52]. No studies have assessed the impact of iron replacement on prognosis, but two open-label protocols have demonstrated improved aerobic capacity following intravenous iron, most probably due to improved skeletal muscle mitochondrial oxidative capacity [53,54]. Data were not reported on dyspnoea specifically, but improvements were seen in both studies in quality of life as assessed by the SF-36 score (36-item Short-Form Health Survey).…”
Section: Impact Of Comorbidities On Exercise Limitation/breathlessnesmentioning
confidence: 99%
“…It has been suggested that iron deficiency is not just a marker of severity, but independently contributes to poor prognosis and exercise function [52]. No studies have assessed the impact of iron replacement on prognosis, but two open-label protocols have demonstrated improved aerobic capacity following intravenous iron, most probably due to improved skeletal muscle mitochondrial oxidative capacity [53,54]. Data were not reported on dyspnoea specifically, but improvements were seen in both studies in quality of life as assessed by the SF-36 score (36-item Short-Form Health Survey).…”
Section: Impact Of Comorbidities On Exercise Limitation/breathlessnesmentioning
confidence: 99%
“…Iron containing protein is also required for mitochondrial electron transport and catalyzes reactions that form NO[169]. Intravenous iron therapy in patients with idiopathic PAH was well tolerated and it improved endurance capacity; however, it did not alter cardiac function[170]. Thus, iron deficiency seems to be a more important prognosticator compared with anemia.…”
Section: Iron Homeostasis and Pahmentioning
confidence: 99%
“…Recently, iron in PH patients has become an everincreasing focus for research with the general concept that iron deficiency is associated with disease phenotype [5,6]. In addition, intravenous iron therapy improves exercise endurance capacity in patients with idiopathic PH and iron deficiency [13]. However, it remains completely unknown whether PH leads to iron deficiency or iron deficiency enhances the development of PH.…”
Section: Discussionmentioning
confidence: 99%